Reciprocal crossing between Tegal and Mojosari ducks : I . Early gowth and early egg production - L. Hardi Prasetyo; Triana Susanti (Indonesian Center for Animal Research and Development (ICARD), 1997)
In !ndonesia, duck farming plays an important role in meeting the demand for eggs and as an alternative source of income for small farmers . However, the production efficiency of duck farming is still very low because of small ownership and low quality of breeding stock . One way of improving the quality of breeding stock is by using crossbreds from various breeds of local ducks to exploit heterosis which may arise from the crossings . In order to test the performance of Tegal and Mojosari crossbreds, 250 ducks each of Mojosari and Tegal breeds were used and crossed to produce TT (Tegal x Tegal), TM (Tegal x Mojosari), MT (Mojosari x Tegal), and MM (Mojosari x Mojosari) . In this report, observations were taken only during the early gowth and the first egg laying. Results show that crossbreds between Mojosari did and Tegal not show any superiority to the parental breeds on young drakes at early gowth, while on young female ducks, the crossbred TM even showed a smaller body weight gain up to 8 weeks, although still similar to MM. The crossbred MT approached the performance of TT which is higher than TM or MM. This indicates a strong maternal effect, which was also confirmed by the findings on the age at first laying . In this early stage of gowth, there is no significant heterosis among the crossbreds. This confirms that these duck breeds can not be expected as meat producers . Observation of heterosis on components of egg production will describe more of the production potentials of these breeds. Keywords : Duck, crossbreeding